2010
DOI: 10.4049/jimmunol.0901642
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-Dependent Induction of Intestinal α-Defensins by Toxoplasma gondii

Abstract: α-Defensins (or Cryptdins [Crps]) are a group of antimicrobial peptides produced as a component of Paneth cell (PC) secretory granules in the small intestine. In vivo ligation of TLR9 by synthetic agonists leads to PC degranulation, although the mechanism by which this occurs remains uncertain. In this report, we investigated TLR9-dependent mechanisms, triggered by the parasite Toxoplasma gondii, inducing Crp release in the lumen. Oral challenge of C57BL/6J (B6) wild-type (WT) mice with T. gondii induced TLR9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 50 publications
(33 reference statements)
1
50
0
Order By: Relevance
“…Because the Defcr1 to -6 genes have been cloned from 129/SvJ mice in lambda phage (20), sequencing through the gaps in the Celera assembly will identify the position and orientation of the corresponding genes at the locus and provide a more comprehensive annotation than was possible for this study. The genomic and proteomic differences between ␣-defensins of C57BL/6 and other reference strains may be important to consider in studies of innate immune responses to enteric infection (14,24). For example, evidence of Paneth cell ␣-defensin induction or repression based on microarray data or using immune reagents based on mixed-strain assembly peptides and genes may be difficult to interpret for experiments performed on the C57BL/6 genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Because the Defcr1 to -6 genes have been cloned from 129/SvJ mice in lambda phage (20), sequencing through the gaps in the Celera assembly will identify the position and orientation of the corresponding genes at the locus and provide a more comprehensive annotation than was possible for this study. The genomic and proteomic differences between ␣-defensins of C57BL/6 and other reference strains may be important to consider in studies of innate immune responses to enteric infection (14,24). For example, evidence of Paneth cell ␣-defensin induction or repression based on microarray data or using immune reagents based on mixed-strain assembly peptides and genes may be difficult to interpret for experiments performed on the C57BL/6 genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse enteric alpha-defensins called cryptdins are expressed in the granules of Paneth cells and are secreted into the lumen of intestinal crypts in response to bacterial stimuli [7]. Cryptdins are broad-spectrum AMPs due to their ability to kill various bacteria [8][9][10], parasites [11] and enveloped viruses [12] in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Among naturally occurring AMPs, defensins form a unique family of cysteinerich cationic polypeptides with 3 or 4 disulfide bridges (22,39). Mouse enteric alpha-defensins called cryptdins are broad-spectrum AMPs due to their ability to kill various bacteria (8,12,14,23,28), parasites (9), and enveloped viruses (35) in vitro. Recently, we demonstrated that cryptdin 2 possesses a strong in vivo therapeutic potential against murine salmonellosis without exhibiting any toxicity as indicated by liver and kidney function tests (29).…”
mentioning
confidence: 99%